Family-centered approach in Early Childhood Intervention of a vulnerable population from an Ecuadorian rural context - Frugone-Jaramillo, Marcela; Gràcia, Marta (Frontiers in Psychology, 2023)
Introduction. Studies about the implementation of the Family Centered Practices approach in Early Childhood Intervention refer as outcomes that have an impact on the Quality of Family Life, on children's development, and also on family empowerment. In Ecuador, despite an absence of Early Childhood Intervention policies and programs, a university has developed training in Family Centered Practices for graduate students. A formative component is to implement a Routines Based Model with families of children with disabilities. The aim of the study is to analyze the impact on the Family Quality of Life, children's development and self-perceived competence of families after the Routines Based Model has been implemented in their natural environment. Method. Eight families from a rural area and their children with disabilities were included in the study. The Family Quality of Life Scale-Early Childhood Intervention and the Screening of the Battelle Developmental Inventory were applied at the beginning and end of the process. A qualitative interview established the family perspective upon the outcomes in their family and their children. Results. There is evidence of a significant increase in the families' Quality of Life and in the children's development at the end of the process. At the interview the families declared themselves more competent to understand and contribute to the development of their children. Discussion. The results provide knowledge of the implementation of a Routine Based Model in vulnerable contexts. Also contributes in the understanding of the family perspective on the outcomes and perceived benefits for the children and the family itself as a measure of quality of the intervention and training. Implications of the results for initial and ongoing training of early care professionals with vulnerable populations are discussed.